2021
DOI: 10.3390/ijms22073467
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A2A Receptors Are Upregulated in Peripheral Blood Mononuclear Cells from Atrial Fibrillation Patients

Abstract: Atrial fibrillation (AF) is the most common form of cardiac arrhythmia seen in clinical practice. While some clinical parameters may predict the transition from paroxysmal to persistent AF, the molecular mechanisms behind the AF perpetuation are poorly understood. Thus, oxidative stress, calcium overload and inflammation, among others, are believed to be involved in AF-induced atrial remodelling. Interestingly, adenosine and its receptors have also been related to AF development and perpetuation. Here, we inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 39 publications
2
18
0
Order By: Relevance
“…We observed a correlation between adenosine receptor expression in PBMCs and atria regardless of the subtype considered. These data also confirmed that PBMCs are a useful model for studying the adenosinergic system of AF patients (23). Finally, we do not observe a significant correlation between BAC and LA receptor production.…”
Section: Discussionsupporting
confidence: 87%
“…We observed a correlation between adenosine receptor expression in PBMCs and atria regardless of the subtype considered. These data also confirmed that PBMCs are a useful model for studying the adenosinergic system of AF patients (23). Finally, we do not observe a significant correlation between BAC and LA receptor production.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, a higher adenosine plasma level in the left atria has been shown to be associated with AF episodes that normalize after cardioversion [ 75 ]. High A 2A R production in an AF patient’s atria was also reported [ 76 , 77 ]. In particular, an increased adenosine blood level, reduced adenosine deaminase activity, and upregulation of A 2A R of PBMC have been reported in patients with AF.…”
Section: Possible Clinical Consequences Of the Presence Of Spare Receptorsmentioning
confidence: 72%
“…In particular, an increased adenosine blood level, reduced adenosine deaminase activity, and upregulation of A 2A R of PBMC have been reported in patients with AF. In addition, a positive and significant correlation between A 2A R production in the right atrium and in PBMC was observed [ 77 ].…”
Section: Possible Clinical Consequences Of the Presence Of Spare Receptorsmentioning
confidence: 99%
“…An important issue that needs to be addressed concerns the specificity of this adenosine receptor subtype as a potential biomarker of AD. Regarding specificity in particular, an upregulation of them was already found in lymphocytes from ischemic stroke patients [ 112 , 113 , 114 ], amyotrophic lateral sclerosis and multiple sclerosis [ 115 , 116 ], Huntington’s and Parkinson’s disease [ 106 , 117 ], chronic heart failure and cardiac transplantation [ 105 ], and in PMBCs from atrial fibrillation patients [ 118 ]. In spite of this wide overexpression of A 2A receptors in lymphocytes and neutrophils of patients with pathologies of different nature and affecting different organs, the evidence related to their upregulation in AD has been relieved in platelets, and whether the same result is present in lymphocytes has yet to be determined.…”
Section: A 2a Adenosine Receptor As a Novel Peripheral Biomarker In Admentioning
confidence: 99%